2007
DOI: 10.1007/bf03022771
|View full text |Cite
|
Sign up to set email alerts
|

La technique anesthésique n’affecte pas la performance d’un modèle de réductions cycliques de flot chez le lapin : une étude pilote

Abstract: Purpose: Pentobarbital anesthesia is, typically, used in an experimental model of cyclic flow reductions (CFR) in rabbits. Our initial observations, using a more complete and effective isoflurane-based anesthetic technique, failed to reproduce findings reported previously. Consequently, we compared the effects of these two anesthetic techniques in the model. Methods:A modified Folts' model of carotid artery lesion and stenosis was used. Twelve rabbits completed the experimental protocol: five in the pentobarbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Considering that PCC and rFVIIa may promote thrombosis, we used our model to evaluate their safety. As reported by others, 35 and in a previous work, 25 we observed that CFRs nearly disappeared after haemodilution. The lack of a significant increase in CFRs after PCC and rVIIa infusion is reassuring, suggesting that PCC appears to be as safe as rFVIIa.…”
Section: Bjasupporting
confidence: 90%
“…Considering that PCC and rFVIIa may promote thrombosis, we used our model to evaluate their safety. As reported by others, 35 and in a previous work, 25 we observed that CFRs nearly disappeared after haemodilution. The lack of a significant increase in CFRs after PCC and rVIIa infusion is reassuring, suggesting that PCC appears to be as safe as rFVIIa.…”
Section: Bjasupporting
confidence: 90%
“…Regarding the effect of decoys on thrombosis in the rabbit, the hypothesis based on results from our in vitro study was that the decoys would induce thrombosis inhibition. Specifically, n = 6 replicates were initially selected for determination of the effect of 20% decoys on thrombosis in the rabbit based on reference (35); however, on the basis of data collected in our study, we carried out studies with 40% decoys to see whether we could further inhibit thrombosis. This design led to groups with n = 6, 6, 4, and 2 replicates for saline, 20% decoys, 20% platelets, and 40% decoys, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Both common carotid arteries (CCAs) were exposed through a ventral midline neck incision and Transonic vascular flow probes were positioned on the distal CCAs. Thrombotic events were monitored over 2 hours after CCA injuries, and CFRs with flow velocity greater than 5 ml/min were quantified (35).…”
Section: Thrombosis Model In New Zealand Rabbitsmentioning
confidence: 99%